People Awareness on Diabetes Disease and Complications in Bushehr, Iran Using Linears Models - Afkhami Ardekani M; Bahreini F; Rabieian M; Khalkhaly HR; Soltanian AR; Babaee QR (Tehran University of Medical Sciences, 2007)
Backgound: Approximately half of the diabetics population type 2 are not aware of their disease .Lack of awareness can lead to development of diabetes and increase cost of treatment. The aim of this survey was to determine the level of population awareness in Bushehr port in south of Iran in Bushehr province.Methods: In this cross-sectional study, 719 subjects (417 male and 302 female) aged over 18 years old, without diabetes and inhabitant in Bushehr port in 2005 were assessed. Multi-stage random simple sampling was used. A 39 question questionnaire was used with validity checked by researchers in Yazd Diabetes Research Center and reliability alpha-cronbach=75%.The data were analyzed with independent t-test, pearson correlation coefficient , ANOVA and Multiple Logistic Regression models by SPSS package ver. 10.05.Results: Mean and SD of scores of subjects knowledge levels were 16.96 and 6.29, respectively. The levels of males' awareness rate was more than females' (P=0.001). There was indirect relation between subjects awareness and their age (r=-0.203, P=0.001) and direct relation between awareness and the level of education (P=0.01, r=0.07).The mean of awareness scores was not similar between singles and married (P=0.042). Awareness regarding fundamental diabetes disease, primary symptoms, early complications, delay complications, diet awareness was low and concerning controlling methods of diabetes was high.Conclusion: Awareness in relation to fundamental and complications of diabetes disease was low, so the people need more education about diabetes.